Standardization, Calibration, and Control in Flow Cytometry. Issue 1 (5th January 2017) - Wang, Lili; Hoffman, Robert A.
Abstract: Because flow cytometers are designed to measure particle characteristics, particles are the most common materials used to calibrate, control, and standardize the instruments. Definitions and cautions are provided for common terms to alert the reader to critical distinctions in meaning. This unit presents extensive background on particle types and cautions and describes practical aspects of methods to standardize and calibrate instruments. Procedures are provided to characterize performance in terms of optical alignment, fluorescence and light scatter resolution, and sensitivity. Finally, suggestions follow for analyzing particles used for calibration. © 2017 by John Wiley & Sons, Inc.